2017
DOI: 10.1021/acscatal.7b00251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TiO2 Bulk Defects on CO Adsorption and CO Oxidation on Au/TiO2: Electronic Metal–Support Interactions (EMSIs) in Supported Au Catalysts

Abstract: Electronic metal−support interactions (EMSIs) are demonstrated to severely affect the CO oxidation activity and the CO adsorption properties of Au/TiO 2 catalysts. Bulk oxygen vacancies, generated by a strongly reductive pretreatment of Au/TiO 2 at elevated temperature in 10% CO/N 2 , significantly lower the catalytic activity for CO oxidation at 80 °C. With time on stream, the activity slowly increases until reaching the same steady-state value as that obtained for a previously calcined and, hence, defect-poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 58 publications
9
133
2
Order By: Relevance
“…Camellone and Fabris demonstrated that the oxygen vacancy deactivated the Au/CeO 2 catalysts and thus prevented further CO adsorption . Wang et al demonstrated by combined kinetic and in situ IR spectroscopic measurements that the presence of bulk oxygen vacancies reduced the catalytic activity of Au/TiO 2 in CO oxidation . Eyrich et al produced different types of Au/TiO 2 catalysts to address the issue that the segregation of Ti interstitials instead of oxygen vacancy in subsurface regions promoted catalytic activity, in agreement with the work regarding the influence of Ti interstitials in ref.…”
Section: Introductionsupporting
confidence: 62%
“…Camellone and Fabris demonstrated that the oxygen vacancy deactivated the Au/CeO 2 catalysts and thus prevented further CO adsorption . Wang et al demonstrated by combined kinetic and in situ IR spectroscopic measurements that the presence of bulk oxygen vacancies reduced the catalytic activity of Au/TiO 2 in CO oxidation . Eyrich et al produced different types of Au/TiO 2 catalysts to address the issue that the segregation of Ti interstitials instead of oxygen vacancy in subsurface regions promoted catalytic activity, in agreement with the work regarding the influence of Ti interstitials in ref.…”
Section: Introductionsupporting
confidence: 62%
“…Supported metal catalysts are extensively employed in many industrial reactions including ammonia synthesis, selective hydrogenation, selective oxidation, and steam reforming . Great effort has been focused on tailoring the metal active sites so as to simultaneously enhance the catalytic performance, selectivity, and stability.…”
Section: Supported Metal Catalysts Derived From Ldh Precursorsmentioning
confidence: 99%
“…[24][25][26] Interaction of the CO probe molecule with the Au sites is weak and reversible. [24,25,[28][29][30] The CO-adsorbate spectra measured at À160 8C for freshly prepared TiO 2 -based catalysts are displayed in Figure 4a.I na ll catalysts ab and around 2125 cm À1 can be seen with as houlder around 2108 cm À1 .T he latter band is assigned to nAu 0 ÀCO, whereas the band around2 125 cm À1 is relatedt o the CO adsorbed on Au d+ + sites. [24,25,[28][29][30] The CO-adsorbate spectra measured at À160 8C for freshly prepared TiO 2 -based catalysts are displayed in Figure 4a.I na ll catalysts ab and around 2125 cm À1 can be seen with as houlder around 2108 cm À1 .T he latter band is assigned to nAu 0 ÀCO, whereas the band around2 125 cm À1 is relatedt o the CO adsorbed on Au d+ + sites.…”
Section: Characterization Of Fresh and Used Catalystsmentioning
confidence: 99%
“…[27] Therefore, the adsorption of CO is preferentially performed at low temperatures as it is well known that supported Au catalysts are able to oxidize CO not only at room temperature but also at significantlyl ower temperatures. [24,25,[28][29][30] The CO-adsorbate spectra measured at À160 8C for freshly prepared TiO 2 -based catalysts are displayed in Figure 4a.I na ll catalysts ab and around 2125 cm À1 can be seen with as houlder around 2108 cm À1 .T he latter band is assigned to nAu 0 ÀCO, whereas the band around2 125 cm À1 is relatedt o the CO adsorbed on Au d+ + sites. [28,31,32] The intensity ratio of theset wo bands differs depending on the alkali promotor.T hus, the lower frequency band is more intense in the Cs-loaded samples, which confirms that the formation of Au 0 sites is promoted by Cs.…”
Section: Characterization Of Fresh and Used Catalystsmentioning
confidence: 99%